2014
DOI: 10.1523/jneurosci.4713-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Intestinal Polypeptide Mediates Circadian Rhythms in Mammalian Olfactory Bulb and Olfaction

Abstract: Accumulating evidence suggests that the olfactory bulbs (OBs) function as an independent circadian system regulating daily rhythms in olfactoryperformance.However,thecellsandsignalsintheolfactorysystemthatgenerateandcoordinatethesecircadianrhythmsareunknown. Using real-time imaging of gene expression, we found that the isolated olfactory epithelium and OB, but not the piriform cortex, express similar, sustained circadian rhythms in PERIOD2 (PER2). In vivo, PER2 expression in the OB of mice is circadian, approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 28 publications
5
49
1
Order By: Relevance
“…Additionally, online bioluminescence measurements in OE tissue explants displayed rhythmic PER2 expression patterns over several days. This is in agreement with observations in other peripheral tissues, which oscillate over the course of several days (Yoo et al, 2004) and with findings from OE explants recently reported by Miller et al (2014). In further support of an OE clock, we demonstrated that PER2 protein is expressed rhythmically ex vivo and displays circadian variation in cell bodies and dendritic knobs of OSNs.…”
Section: Olfactory Sensory Neurons Possess An Autonomous Circadian Clocksupporting
confidence: 93%
“…Additionally, online bioluminescence measurements in OE tissue explants displayed rhythmic PER2 expression patterns over several days. This is in agreement with observations in other peripheral tissues, which oscillate over the course of several days (Yoo et al, 2004) and with findings from OE explants recently reported by Miller et al (2014). In further support of an OE clock, we demonstrated that PER2 protein is expressed rhythmically ex vivo and displays circadian variation in cell bodies and dendritic knobs of OSNs.…”
Section: Olfactory Sensory Neurons Possess An Autonomous Circadian Clocksupporting
confidence: 93%
“…In particular, in plants, the core transcriptional NFL consists of series of transcriptional repressions, which has a similar design as the repressilator or quadripressilator [5,[171][172][173]. While the detailed transcriptional repression mechanism has not been fully identified, currently models have assumed Hill-type repression [171,[174][175][176][177].…”
Section: While This Review Focuses On Neurospora Drosophila and Mammmentioning
confidence: 99%
“…Structural evidence for synaptic scaling comes from Drosophila in which decreased synapse number and size may be observed after sleep (Bushey et al 2011 At the molecular level, circadian modulation of memory could occur at multiple levels through regulation of sensory gating, neurotransmission, kinase signaling cascades, macromolecular synthesis, or epigenetic modifications. Circadian gating of sensory processes, as observed for olfaction in insects (Krishnan et al 1999) and mammals (Granados-Fuentes et al 2006;Miller et al 2014), could alter salience and perception of sensory stimuli resulting in differential learning acquisition. Downstream, molecular processes can serve as a bridge between the circadian clock and memory either through circadian regulation of basal expression and activity levels, rhythms in cellular compartmentalization, or rhythms in training-inducible activity or expression (Table 1).…”
Section: Mechanisms Linking the Circadian Clock And Memorymentioning
confidence: 99%
“…This hierarchy stands in contrast to the circadian system in lower vertebrates such as fish or invertebrates, e.g., Drosophila melanogaster, in which independently entrainable oscillators may be found throughout the organism (Plautz et al 1997;Whitmore et al 2000). Nonetheless, even in mammals independent peripheral oscillators exist including the food-entrainable oscillator in the liver (Stephan 2002;Saper and Fuller 2007;Mistlberger 2011) and oscillators in the olfactory bulb (Granados-Fuentes et al 2004;Abraham et al 2005;Miller et al 2014). …”
mentioning
confidence: 94%